Effects of inlet and outlet boundary conditions on the flow field of synthetic jets. (April 2017) - Bazdidi-Tehrani, Farzad; Hatami, Mohammad; Abouata, Ahmad
The present work provides the computations of unsteady 3D synthetic jet ejected into a quiescent ambient. TheSST / k - ω turbulence model is employed for numerical simulations of flow field and the problem is considered under incompressible and axisymmetric assumptions. The pressure-implicit with splitting of operators algorithm is used for coupling of continuity and momentum equations. In order to accurately simulate the synthetic jet actuator, the dynamic mesh method is employed to model the flow field. In different simulations, pressure inlet, pressure outlet and wall boundary conditions at the orifice outlet of the synthetic jet are investigated. Changes in the boundary conditions at the orifice outlet affect the flow field such that mean velocity magnitude is higher for unconfined synthetic jets than confined ones. Moreover, form of vortex rings is dissimilar for confined and unconfined jets. Also, the actuator is modelled with two types of inlet boundary conditions, namely, moving piston and moving diaphragm boundaries. Results show that they have no significant difference and can be used interchangeably.